Insegnare moduli di "Arte, Scienze e Tecnologie di Rappresentazione Grafica”: quali sfide per il futuro? - Lo Tauro, Agata (GEOmedia, 2014)
The battle between neo-idealists and scientists at the turn of the XX century that resulted in stereotypes about the role of science in Italian education has survived mo re or less unchanged and unchallenged to these days. This app roach has created a situation in which a traditional method on research and experimentation is now required based on the different needs of each student, as well as those of tod ay's markets. Professors therefore need to develop skills to enable students to visualise and interpret "reality” (e.g. Natural and Cultural Heritage) in order to co ntribute to other disciplines, in particular within the co ntext of an Open Knowledge and Content and Language Integrated Learning (CLIL ) "novel app roaches”. This exercise isn't simp ly design based, but requires several aproaches such as the reclassification of schoo ls and educational institutions not simp ly as voc ational and technical edpucational establishments, but mo tivational too , thus mo re closely respo nding to soc ietal needs. Detecting social dependencies in this co ntext requires comp etent "educators” who aren't just following well trodd en paths, but are able to provide an authentic dialogue, as well as consistency of expression, even encomp assing lifestyle choices. Such holistic approach needs to be framed in the co ntext of lifelong learning, and also away from simp ly forprofit models but in the direction too of not for profit organisations. In this particular circumstances an adequate developm ent of effective third sector personnel will require skills that are better acquired through the proc esses just mentioned. The research co llaboration between educational institutions will provide impo rtant findings to inform imp rovements to imp lement educational strategies and overall design of novel research projects. We are loo king forward to embarking on this project and seeing how the research results will influence the Science and technologies for graphical representation, both in Europ e and internationally. This is a work-in progress.